Improving Defect Tire Curing Process With Six Sigma Method at Tire Manufacturing Industry - Santo Wibowo; Humiras Hardi Purba (Universitas Mercu Buana, 2019)
The tire manufacturing process, the tire company's amount of defect tends to increase above the target maximum. To improve the quality of tire manufacture, and analysis to decrease the number of defects is conducted using the six sigma concept. Over the last two decades, there has been a growing awareness of the need to improve quality. This paper aims to implement the DMAIC cycle as an element of continuous improvement in tire companies. In order that achieves it, the analysis with the application of DMAIC is done. The propositions of improvements, which can be implemented in the organization to increase the effectiveness of the production process, are also presented. The actions implemented contributed to a significant reduction in the defective tire, which was approximately 67 pcs per month. The study thus culminated in a decrease of 0,08% on the indicator of defects by the production system